Food Safety: Play It Safe with Eggs - Jennifer Hillan (EDIS)
Revised! FCS8635, a one-page fact sheet by Jennifer Hillan, reviews important food safety principles that should be followed when cooking with and eating eggs and foods made with eggs. Published by the UF Department of Family, Youth and Community Sciences, August 2006.